EMPIRICAL RESEARCH: THE IMPACT OF FOOD SECURITY ON ECONOMIC GROWTH (CASE STUDY IN INDONESIA) - Wendra Hartono; David Sukardi Kodrat; Damelina Basauli Tambunan; Isadora Elgina Pramana; Juan Richard Alexander (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Abstract: The world is perceived to be experiencing an acute food crisis which will continue until 2023. The Ministry of Finance of the Republic of Indonesia estimated that the upcoming global economic growth will weaken. Drops in the economy can be influenced by the uncertain global financial markets, inflationary pressures, increasing stagflation rate, and geopolitical situations. The problem research is: Does food security have an impact on Indonesia's economic growth? This study adopts real GDP (Y) as a proxy for economic growth; labor force (Lf) as a proxy for labor; Gross Capital formation (CI) as a proxy for capital; food production index (FS) as a proxy for food security; and trade openness (TO) is proxied by the sum of total export and total import divided by real GDP. This study examines and compares the impact of food security on economic growth in Indonesia using VECM method using 30 years of data, ranging from 1991 to 2020. The estimated results signified that food security in Indonesia plays a pivotal role in stimulating economic growth although the level of influence varies.